Analysis of the possibility of managing the database stored in the cloud - Góźdź, Rafał; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2016)
The article presents a comparative analysis of the performance of selected database systems. The time of execution of SQL statements has been compared by prepared database service which are running in the cloud. Prepared Northwind database running on SQL Server has been moved to systems Oracle and PostgreSQL, and then three of these bases have been placed in the cloud Microsoft Azure. The research process was divided into three stages. Firstly, queries with Select are analyzed. In the second stage, the analysis focuses on the performance of SQL DDL, and the final stage of the analysis describes the SQL DML.